2019
DOI: 10.1186/s12933-019-0934-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1 year of exercise training versus combined exercise training and weight loss on body composition, low-grade inflammation and lipids in overweight patients with coronary artery disease: a randomized trial

Abstract: Background Dyslipidaemia and low-grade inflammation are central in atherogenesis and linked to overweight and physical inactivity. Lifestyle changes are important in secondary prevention of coronary artery disease (CAD). We compared the effects of combined weight loss and interval training with interval training alone on physical fitness, body composition, dyslipidaemia and low-grade inflammation in overweight, sedentary participants with CAD. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 57 publications
3
52
0
3
Order By: Relevance
“…For instance, without weight loss, a twice-weekly progressive aerobic program in patients with T2DM did not observe any changes in TNF-α and CRP levels following a 6-month intervention [31], which follows our findings. On the other hand, a 1-year aerobic exercise intervention plus weight loss [32] showed a significant reduction in both TNFα and CRP. Moreover, in overweight/obese individuals without T2DM, short and medium-term interventions have also observed a reduction in IL-6 following 2 weeks [33], and 16 weeks of HIIT [34], where modest weight loss was observed.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, without weight loss, a twice-weekly progressive aerobic program in patients with T2DM did not observe any changes in TNF-α and CRP levels following a 6-month intervention [31], which follows our findings. On the other hand, a 1-year aerobic exercise intervention plus weight loss [32] showed a significant reduction in both TNFα and CRP. Moreover, in overweight/obese individuals without T2DM, short and medium-term interventions have also observed a reduction in IL-6 following 2 weeks [33], and 16 weeks of HIIT [34], where modest weight loss was observed.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, T2DM per se is not an official indication for performing CPET, a population in which the 6 min walking test is often seen as the first choice-since it is validated against exercise test [ 138 ]-yet quite uninformative. On the contrary, CPET allows a precise estimate of oxygen dynamics (which is also preserved in patients with coronary artery disease, appearing safe and very informative-even at very reduced workloads [ 139 ]), together with a multivariable cardiopulmonary, muscular and metabolic assessment; therefore, it might be envisaged not only for the assessment of cardiorespiratory fitness, but also for HF risk stratification and rehabilitation prescription and surveillance alike.
Fig.
…”
Section: Future Directionsmentioning
confidence: 99%
“…Accordingly, promotion of increased physical activity and exercise training is essential for CHF patients with T2DM to improve cardiorespiratory fitness and reduce cardiovascular or all-cause mortality. Indeed, various types of exercise training including moderate-intensity continuous training and high-intensity interval training are reported to improve cardiac function, vascular function, lipid profiles, and low-grade inflammation as well as exercise capacity in obese subjects or patients with T2DM [35][36][37][38] and in patients with CHF [39]. A large clinical trial has shown that sustained improvement of exercise capacity by intensive lifestyle intervention aiming at increased physical activity and weight loss reduces risk of incident HF in obese subjects with T2DM [40].…”
Section: Table 4 Multivariable Analysis For Peak Vo 2 In the Chf Patimentioning
confidence: 99%